ḌAʿĪF JIDDAN VS. MAWḌŪʿ: A COMPARATIVE ASSESSMENT OF ḤADĪTH BY IBN AL-JAWZĪ IN AL-MAWḌŪʿĀT AND AL-ʿIRĀQĪ IN AL-MUGHNĪ ʿAN ḤAML AL-ASFĀR FĪ AL-ASFĀR - Marwan Mas'ud Mas'ud; Imam Ghazali Said; Mohammed Alghiffar Alwalid (Al-Majaalis : Jurnal Dirasat Islamiyah, 2025)
This study explores the methodological differences in ḥadīth classification between al-ʿIrāqī and Ibn al-Jawzī, prompted by the broader discourse on the authenticity of Islamic traditions. The research primarily compares five aḥādīth judged as ḍaʿīf jiddan by al-ʿIrāqī and as mawḍūʿ by Ibn al-Jawzī, focusing on their distinct approaches in evaluating isnād and matn. A secondary focus lies in examining al-ʿIrāqī’s precision in takhrīj and isnād analysis versus Ibn al-Jawzī’s critical stance toward unreliable transmitters and implausible texts. This qualitative, descriptive-comparative study adopts a library-based approach and deductive reasoning, relying on primary and secondary sources within the discipline of jarḥ wa-taʿdīl. The research aims to determine which scholar's assessment aligns more accurately with the standards of ḥadīth criticism. The findings reveal that one narration concerning the virtue of bread is more appropriately classified as ḍaʿīf jiddan, while the remaining four about ʿUmar ibn al-Khaṭṭāb’s virtues, curbing desires, bringing goods from the market, and generosity are best regarded as mawḍūʿ. These results highlight the richness of the ḥadīth critical tradition and affirm that ḥadīth authority in Islam must rest on rigorous scholarly verification, balancing both isnād reliability and matn coherence.